Kinetics And Mechanism Of The Cleavage Of N-Methoxyphthalimide (NMPT) In The Presence Of Buffers Of Tris (Hydroxymethyl)Amino-Methane (Tris) And 1,4-Diazabicyclo 2.2.2 Octane (DABCO) - Khan, M.N.; Ariffin, Azhar (2003)
The magnitude of hydroxide ion-catalyzed second-order rate constant (k(OH)) for hydrolysis of N-methoxyphthalimide (NMPT) supports the conclusion that the rate law for pH-independent hydrolysis of N-hydroxyphthalimide (NHPTH) is rate = k(OH)[HO-][SH], where SH represents nonionized NHPTH. The second-order rate constants for the reactions of NMPT with DABCO and Tris are (59.7 +/- 6.9) x 10(-3) and (11.9 +/- 2.3) x 10(4) M-1 s(-1), respectively.